SENTUHAN KEPADA LANSIA MELALUI PROGRAM PERMAKANAN DI KELURAHAN GEBANG PUTIH, KECAMATAN SUKOLILO, SURABAYA - Widyastuti, Maria; Dimalouw, Jefri Eriks (STIE Mahardhika, 2020)
Surabaya City government implements article 34 paragraph 1 CONSTITUTION 1945 with Food program, which is given to the underprivileged community.  The food Program started in 2012, the number of food recipients in 2019 has reached 35,414 people. Details, elderly and pre-elderly 20,000 people, orphans, orphans and orphans as many as 6,000 children, as well as a disability of 9,414 people. In Kelurahan Gebang Putih There are 84 food recipients who all consist of the elderly. The food program is very helpful to the elderly to fulfill the needs of primary food, but as good as the program, still leave some issues, among others: the food served is less liked by the recipient because of the physical condition and age, many places to eat the edges are broken and often disappear and food sanitation is less hyginical. To solve the problem: it should be often conducted a meeting between the Dinsos and a food provider who is directly faced with the recipient of the meal so that all issues will be quickly addressed according to the authority.